Pengaruh Pemberian Pakan Kombinasi ( Moringa Oliver) Dan Perasan Jeruk Nipis ( Citrus aurantifolia) Terhadap Pertambahan Bobot Badan dan Feed Conversion Ratio (FCR) Ayam Broiler - Bili, Agustinus Mulan; Deta, Herlina U.; Ndaong, Nemay Anggadewi; Novian, Dede R. (Program Studi Kedokteran Hewan, Universitas Nusa Cendana, 2025)
This study aims to determine the effect of adding keloer flour to feed and lime juice in drinking water of broiler chickens on body weight gain, feed consumption and ration conversion of broiler chickens. This study was conducted from August 2022 to November 2022 at the Dry Land Chicken Cage Unit, Nusa Cendana University. This study is an experimental study using the Completely Randomized Design method, consisting of 4 treatments with 6 replications and 3 Reserves for each treatment were added. The number of broiler chickens kept was 36 consisting of 4 treatment groups in a cage with a division of plots for each treatment group. Each treatment group plot was filled with 9 chickens each. The feed given to broiler chickens was CP 11 (1-21 days) and CP 12 (22-35 days) and additional feed combination of moringa flour (Moringa oleifera) and lime (Citrus aurantifolia) with the provisions, for T0 (control treatment) given commercial feed and drinking water, T1 (first treatment) given commercial feed, drinking water, and added 4% moringa flour, T2 (second treatment) given commercial feed, drinking water, and added 4% lime juice, and T3 (third treatment) given commercial feed, drinking water, and added 2% moringa flour and 2% lime juice. Data were analyzed using Analysis of Variance (ANOVA) and Duncan's advanced analysis. The results of this study indicate that the addition of moringa flour in feed and lime juice in drinking water has a significant difference (P < 0.05) in feed consumption and ration conversion of Broiler Chickens but does not provide a significant difference (P > 0.05) in body weight gain of Broiler Chickens.